2015
DOI: 10.1038/bmt.2014.304
|View full text |Cite
|
Sign up to set email alerts
|

High-dose melphalan with autologous stem cell support in refractory Hodgkin lymphoma patients as a bridge to second transplant

Abstract: Persistence of disease after salvage therapy among relapsed or refractory Hodgkin lymphoma (HL) patients predicts poor outcome. Here, we report on 41 HL patients with active disease after salvage therapy and who received high-dose melphalan (HD-PAM) and auto-SCT as a bridge to a second autologous or an allogeneic transplantation between 2002 and 2013 at our center. Disease response was based on 18-fluoro-deoxyglucose-positron emission tomography results in all patients. Overall response rate after HD-PAM was 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Every patient provided informed consent. Nineteen patients were included in previous manuscripts [8][9][10]. Inclusion criteria were: lack of HLA-matched related or unrelated donor; primary refractory or relapsed HL refractory to conventional second-line salvage chemotherapy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Every patient provided informed consent. Nineteen patients were included in previous manuscripts [8][9][10]. Inclusion criteria were: lack of HLA-matched related or unrelated donor; primary refractory or relapsed HL refractory to conventional second-line salvage chemotherapy.…”
Section: Methodsmentioning
confidence: 99%
“…A sequential program was previously shown to be feasible and effective for resistant HL with a 2-year event free survival (EFS) of approximately 50% [7]. We have found that high dose melphalan followed by autologous stem cell transplant (ASCT) represents an effective bridge to second transplant, either autologous or allogeneic [8], with 77% of refractory patients reverted to complete (CR) or partial remission (PR) by melphalan conditioning. Furthermore, we found that unmanipulated haploidentical transplant (Haplo-SCT) with high dose post-transplant cyclophosphamide (PT-Cy) was a potential effective strategy with a 3-year PFS and OS of 63 and 77%, respectively [9].…”
Section: Introductionmentioning
confidence: 99%
“…Patients achieving PET-negativity after a second salvage regimen may do well with autologous SCT even though they were PET-positive after the first salvage regimen 47. However, retrospective data in the setting of haploidentical SCT report a low TRM and suggest the existence of clinically relevant, graft-induced immune effects, thus suggesting that allogeneic SCT can be offered to chemorefractory cHL patients, as well as to those patients who fail autologous SCT and achieve CR or PR using novel agents 61. Despite the reduction of NRM and GVHD, disease relapse still represents the major issue in the setting of allogeneic SCT failure.…”
Section: Discussionmentioning
confidence: 99%
“…20 Additionally, because the H96 trial was not a randomized study comparing single versus tandem ASCT, tandem ASCT can only be considered an option for poor-risk patients. Various treatment strategies to improve outcomes after ASCT have been investigated, including PET-adapted approaches, 21,22 dose-intensity of salvage treatment, 23 radiation therapy after ASCT, 24 tandem autoalloSCT, 25 or consolidation with brentuximab vedotin (BV). 26 Recently, the AETHERA randomized trial showed that early consolidation with BV versus placebo after ASCT improved 2-year PFS in patients with HL with risk factors for relapse or progression after transplantation (63% versus 51%, respectively; hazard ratio 0,57; P=0.0013).…”
Section: A B D Cmentioning
confidence: 99%